Insufficient Samples in Office Endometrial Biopsies: Incidence, Risk Factors and Outcomes of Repeat Procedures - Lateefa Othman Aldakhil (Nigerian Journal of Medicine)
Aims: The aim of the study was to evaluate the prevalence and risk factors of insufficient samples in office endometrial biopsies, and the outcomes of repeat biopsies. Settings and Design: This study was conducted in a gynaecological outpatient clinic. A retrospective chart review was performed on patients who underwent office endometrial biopsies. Subjects and Methods: This is a retrospective study analysing 1826 endometrial biopsies performed in a healthcare institution from 2011 to 2017. Statistical Analysis Used: Statistical analyses used SPSS version 23 included one-way ANOVA, Chi-square tests and t-tests to examine relationships between various study variables and abnormal uterine bleeding (AUB), with significance set at P ≤ 0.05. Results: The study found that 16% of initial biopsies yielded insufficient samples, with a higher prevalence amongst post-menopausal women. Obesity and post-menopausal status were identified as significant risk factors for malignancy. In cases where initial biopsies were inadequate, repeat biopsies were performed in 57.4% of patients, revealing predominantly benign pathology and a malignancy risk of <1%. Conclusions: This study underscores the importance of considering the patients’ menopausal status, and body mass index status when interpreting biopsy reports for insufficient samples. These factors should be given due consideration when deciding to repeat biopsies and during patient counseling to improve the adequacy of samples and reduce the need for repeat procedures. By addressing these variables, healthcare providers can enhance diagnostic accuracy and patient management in cases of AUB.